Application of bulk deformation methods for microstructural and material property improvement and residual stress and distortion control in additively manufactured components - Colegrove, Paul A.; Donoghue, Jack; Martina, Filomeno; Gu, Jianglong; Prangnell, Philip B.; Hönnige, Jan Roman (Elsevier, 2016)
Many additively manufactured (AM) materials have properties that are inferior to their wrought counterparts, which impedes industrial implementation of the technology. Bulk deformation methods, such as rolling, applied in-process during AM can provide significant benefits including reducing residual stresses and distortion, and grain refinement. The latter is particularly beneficial for titanium alloys where the normally seen large prior β grains are converted to a fine equiaxed structure – giving isotropic mechanical properties that can be better than the wrought material. The technique is also beneficial for aluminium alloys where it enables a dramatic reduction in porosity and improved ductility.
Keywords: Titanium; Additive manufacture; Microstructure; Residual stress; Distortion